Archeops in-flight performance, data processing, and map making - Macías-Pérez, J. F.; Lagache, G.; Maffei, Bruno; Ganga, K.; Bourrachot, A.; Ade, Peter A. R.; Amblard, A.; Ansari, R.; Aubourg, E.; Aumont, J.; Bargot, S.; Bartlett, J.; et al. (EDP Sciences, 2007)
Aims.Archeops is a balloon-borne experiment inspired by the Planck satellite and its high frequency instrument (HFI). It is designed to measure the cosmic microwave background (CMB) temperature anisotropies at high angular resolution (~12 arcmin) over a large fraction of the sky (around 30%) at 143, 217, 353, and 545 GHz. The Archeops 353 GHz channel consists of three pairs of polarized sensitive bolometers designed to detect the polarized diffuse emission of Galactic dust. Methods.In this paper we present an update of the instrumental setup, as well as the flight performance for the last Archeops flight campaign (February 2002 from Kiruna, Sweden). We also describe the processing and analysis of the Archeops time-ordered data for that campaign, which led to measurement of the CMB anisotropy power spectrum in the multipole range $\ell$ = 10-700 and to the first measurements of both the polarized emission of dust at large angular scales and its power spectra in the multipole range $\ell$ = 3-70 Results.We present maps covering approximately 30% of the sky. These maps contain Galactic emission, including the Galactic plane, in the four Archeops channels at 143, 217, 353, and 545 GHz and CMB anisotropies at 143 and 217 GHz. These are one of the first sub-degree-resolution maps in the millimeter and submillimeter ranges of the large angular-scale diffuse Galactic dust emission and CMB temperature anisotropies, respectively.